The importance of entrepreneurship in the Peruvian deaf community: A challenge for inclusion - Quijada Lovaton, Karin Janett (2021)
Entrepreneurship is a primary factor for the economic development of the country, and its contribution to the deaf community has a relevant significance. In Peru 7.6% of the total population with disabilities suffer from deafness; However, not all deaf people have access to a decent job, since they do not have basic and higher education studies because they face great communication barriers. In this sense, the research reveals the importance of the undertakings of deaf people as a challenge for labor inclusion through the use of the Peruvian sign language. In this article a literary review analysis is made from different authors, which helps to show the study of entrepreneurship in different aspects: economic, psychological, sociological and business management. In conclusion, to achieve the success of entrepreneurship in the Peruvian deaf community we must raise awareness of accessibility in communication as a tool to facilitate their interaction with society; therefore, public and private entities of the business sector should promote ventures for this group.